Carbon dots in analytical chemistry detection and imaging - Hussain, Chaudhery Mustansar; Kailasa, Suresh Kumar (Elsevier, 2022)
"Carbon Dots in Analytical Chemistry: Detection and Imaging explores recent progress in the field of carbon dots synthesis and properties and their integration with various miniaturized analytical devices for the detection of chemical species and imaging of cells. This book is dedicated to exploring the potential applications of carbon dots in analytical chemistry for clinical microbiology, pharmaceutical analysis and environmental analysis. Sections cover synthetic approaches and properties, sample preparation, analytical techniques for the detection of chemical species, imaging of molecules and cells, and analytical tools for biomedical and food analysis. The will be a valuable book for analytical and materials scientists, physical and chemical scientists, and engineers investigating the use of carbon nanomaterials in their analytical procedures."